E-GOVERNMENT IN TAX SERVICES: THE EFFECTIVENESS OF THE ELECTRONIC FILING SYSTEM - Rizki, Ghina Meilani; Myrna, Ryta; Candradewini, Candradewini (Universitas Padjadjaran, 2024)
This research aims to define and elaborate on the effectiveness of e-government in the Electronic Filing System (E-Filing) at the Tax Service Office (KPP) Pratama Pekanbaru Tampan, Pekanbaru City. The research method utilizes a qualitative approach, and descriptive analysis to elaborate on issues using the theory of e-government effectiveness according to Sigwejo & Pather (2016). This study found that the implementation of E-Government in the form of the Electronic Filing System (E-Filing System) at the Tax Service Office (KPP) Pratama Pekanbaru Tampan has not been effectively and maximally executed. This is due to many taxpayers experiencing difficulties in using the system because of inadequate socialization and training, as well as suboptimal technological facilities. Although public interest in using e-government services is quite high, infrastructure limitations and technical support hinder its usage, resulting in low public satisfaction with this service. To enhance effectiveness, improvements in facilities, socialization, training, and technological infrastructure are required to fulfill public expectations and satisfaction. Based on the analysis conducted, to enhance the effectiveness of the E-Filing System at KPP Pratama Pekanbaru Tampan, it is recommended that socialization and training programs for taxpayers be intensified and sustained, technological infrastructure be improved and enhanced, responsive technical assistance services be provided, periodic system evaluation and improvement be conducted, and feedback from taxpayers be collected and analyzed for further enhancement. The study implies that for the E-Filing System at KPP Pratama Pekanbaru Tampan to be more effective, several key areas need attention and improvement.